Effect of Advanced Glycation End Products on Oxidative Stress and Senescence of Trabecular Meshwork Cells - Park, Cheul Ho; Kim, Jae Woo (Korean journal of ophthalmology, 2012)
To investigate the effect of advanced glycation end products (AGE) on oxidative stress and cellular senescence in cultured human trabecular meshwork cells (HTMC). Primarily cultured HTMC were exposed to 0, 10, 50, 100, 200 µg/mL of glycated bovine serum albumin (G-BSA) for 5 days. Also co-exposed were L-arginine, sepiapterin, and antioxidant N-acetylcysteine (NAC). Cellular survival and production of nitric oxide (NO), superoxide, and reactive oxygen species were assessed by 3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide assay, Griess assay, cytochrome c assay, and dichlorofluorescin diacetate assay, respectively. Senescence-associated β-galactosidase staining was performed to quantify the degree of cellular senescence. G-BSA decreased cellular survival, NO production, and increased superoxide production significantly in a dose-dependent manner. The effects of G-BSA were abolished with co-exposure of L-arginine, sepiapterin, and NAC. G-BSA enhanced cellular senescence accompanied by increased production of reactive oxygen species. G-BSA-induced cellular senescence was suppressed by application of L-arginine, sepiapterin, and NAC. AGE enhances cellular senescence of HTMC accompanied with increased oxidative stress. AGE-induced oxidative stress and cellular senescence could be delayed by application of anti-oxidants.